Turning setbacks into stepping-stones for growth in conservation paleobiology - Wingard, G. Lynn; Schneider, Chris L.; Dietl, Gregory P.; Fordham, Damien A. (Frontiers in Ecology and Evolution, 2024)
Conservation paleobiology is a cross-disciplinary field that utilizes the geohistorical record of past life on Earth to inform present-day decisions in conservation and restoration and assist in planning for future natural resource management. However, information on how past ecosystems and species responded to environmental change over decadal to millennial timescales is rarely incorporated into conservation and restoration decision-making. To heighten awareness among conservation and restoration practitioners of the relevance of geohistorical data and to bridge the gap between research and implementation in conservation paleobiology, we proposed a Research Topic titled “Integrating Conservation Biology and Paleobiology to Manage Biodiversity and Ecosystems in a Changing World”. The 21 articles subsequently published demonstrate the diversity and breadth of geohistorical information available to resource management and the challenges of translating these results into conservation practice and policy. Here we discuss the lessons we learned from editing the Research Topic and suggest a pathway forward for conservation paleobiologists who aspire to generate actionable research results to solve current problems in biodiversity conservation and ecological restoration.